Increasing the Efficiency Significantly of Dye-Sensitized Solar Cells based on ZnO Nanomaterial Photoanode by Doping Titanium - Nashiha Chalvi Syahra, Nashiha Chalvi Syahra; Iwantono, Iwantono; Ari Sulistyo Rini, Ari Sulistyo Rini; Puji Nurrahmawati, Puji Nurrahmawati; Suratun Nafisah, Suratun Nafisah; Marlia Morsin, Marlia Morsin; Romi Fadli Syahputra, Romi Fadli Syahputra (Nispr, 2023)
This work was conducted for fabrication of Dye Sensitized Solar Cells (DSSC) based on ZnO nanomaterials as photoanode and Titanium (Ti) as a dopant material. The aims of this research are to see the effect of adding Ti to ZnO materials on optical, structural, morphological properties and on the efficiency of DSSC based on ZnO. The novelty of this work is the tunable properties of ZnO by varying Ti concentration (0.02 M, 0.04 M and 0.06 M). The properties of ZnO have been analyzed using spectroscopy UV-Vis, X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), and energy dispersive X-ray(EDX). The power conversion efficiency (PCE) of the DSSC was recorded from 0.58% to 2.19%